Workplace Spirituality (WS) and Employee Performance: Mediating Role of Organizational Citizenship behavior - Surendra Mahato; Binod Sah; Shiva Raj Adhikari; Binay Shrestha (Utilitas Mathematica, 2025)
It is a study to understand how Workplace Spirituality (WS), Organizational Citizenship Behavior (OCB) and Employee Performance (EP) are interconnected within the construction companies classified as A-Class in Kathmandu, Nepal. The research design is based on the causal-comparative research and quantitative data achieved with the help of structured questionnaires and a 5-point Likert scale, with the focus on answering the question of whether OCB can mediate the effect of WS on EP. Correlation was used to show positive and strong relationships among WS and EP (r = .832), WS and OCB (r = .807), OCB-EP (r = .755) at 0.01 significant rank. Regressions regulated the fact WS has a significant trait on EP (B = 0.418, p < .01) and so does OCB (B = 0.284, p < .01). There was a positive and statistically insignificant indirect impact of WS to EP via OCB which means that the mediating impact was minimal. The results explain the importance of developing spirituality and citizenship attitudes in workplaces to enhance better performances of work executives. Role of leadership in modeling spiritual values takes centre-stage in influencing discretionary behaviours and ensuring effective running of an organisation in the collectivist cultural practice of Nepal. The research also recommends that spiritual growth and workplace become complementary variables that will enhance employee involvement, satisfaction, and retention in the competitive construction sector. The insights also offer theory and practice since they bring to the fore a complex interplay between spirituality, behaviour and performance.